Phosphorylation-Dependent Regulation of Ca2+-Permeable AMPA Receptors During Hippocampal Synaptic Plasticity - Purkey, Alicia M.; Dell’Acqua, Mark L. (Frontiers in Synaptic Neuroscience, 2020)
Experience-dependent learning and memory require multiple forms of plasticity at hippocampal and cortical synapses that are regulated by N-methyl-D-aspartate receptors (NMDA) and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)-type ionotropic glutamate receptors (NMDAR, AMPAR). These plasticity mechanisms include long-term potentiation (LTP) and depression (LTD), which are Hebbian input-specific mechanisms that rapidly increase or decrease AMPAR synaptic strength at specific inputs, and homeostatic plasticity that globally scales-up or -down AMPAR synaptic strength across many or even all inputs. Frequently, these changes in synaptic strength are also accompanied by a change in the subunit composition of AMPARs at the synapse due to the trafficking to and from the synapse of receptors lacking GluA2 subunits. These GluA2-lacking receptors are most often GluA1 homomeric receptors that exhibit higher single-channel conductance and are Ca2+-permeable (CP-AMPAR). This review article will focus on the role of protein phosphorylation in regulation of GluA1 CP-AMPAR recruitment and removal from hippocampal synapses during synaptic plasticity with an emphasis on the crucial role of local signaling by the cAMP-dependent protein kinase (PKA) and the Ca2+calmodulin-dependent protein phosphatase 2B/calcineurin (CaN) that is coordinated by the postsynaptic scaffold protein A-kinase anchoring protein 79/150 (AKAP79/150).